A new phoretic association: Bursaphelenchus minutus (Nematoda: Parasitaphelenchidae) and Orthotomicus erosus (Coleoptera: Scolitydae) recorded on Pinus pinea (L.). Issue 6 (18th August 2017) - Torrini, Giulia; Strangi, Agostino; Paoli, Francesco; Binazzi, Francesco; Camerota, Manuela; Pennacchio, Fabrizio; Roversi, Pio F.
ABSTRACT: A new phoretic association between Bursaphelenchus minutus and the bark beetle Orthotomicus erosus collected on Pinus pinea is described for the first time. Nematode identification was based on morphological observation and biometric measurements of males and females. Moreover, B. minutus was characterized by ITS sequences and RFLP profile.